Taxonomy of European Damaeidae (Acari: Oribatida) VI. The oribatid mite genus Parabelbella: Redescription of P. elisabhetae and synonymy of Akrodamaeus - Miko, Ladislav; Ermilov, Sergey G.; Smelyansky, Ilya E. (Zootaxa, 2011)
The mite genus Parabelbella Bulanova-Zachvatkina, 1972, one of the poorest known genera of Damaeidae, is redefined on the basis of redescription of P. elisabhetae Bulanova-Zachvatkina, 1967, collected by the authors in Russia and following study of the type material of Bulanova-Zachvatkina. Akrodamaeus Norton, 1979 is considered as a junior synonym of Parabelbella based on the new diagnosis. Altogether 7 known species belong to Parabelbella, with known distribution in Russia, Central Asia and America. Development of the concept of the genus is discussed, concluding that the generic name is available only since the year 1972, when P. crenatosetosa was established as it´s type. It was found that the type species was described by Bulanova-Zachvatkina in 1967 and not in 1957 as earlier presented. Recently proposed synonymies of Heterodamaeus Mihelčič, 1964, Mirobelba Pérez-Iñigo et Peña, 1994, Tectodamaeus Aoki, 1984 and Nododamaeus Hammer, 1977 with Parabelbella are considered unacceptable without additional information and synonymy of Akrodamaeus with Metabelbella Bulanova-Zachvatkina, 1957 is rejected. The key of European species of Parabelbella is given.